Greenland surface mass balance as simulated by the Community Earth System Model. Part II: Twenty-first-century changes - Vizcaíno, Miren (author); Lipscomb, William (author); Sacks, William (author); van den Broeke, Michiel (author) (Journal of Climate, 2014)
This study presents the first twenty-first-century projections of surface mass balance (SMB) changes for the Greenland Ice Sheet (GIS) with the Community Earth System Model (CESM), which includes a new ice sheet component. For glaciated surfaces, CESM includes a sophisticated calculation of energy fluxes, surface albedo, and snowpack hydrology (melt, percolation, refreezing, etc.). To efficiently resolve the high SMB gradients at the ice sheet margins and provide surface forcing at the scale needed by ice sheet models, the SMB is calculated at multiple elevations and interpolated to a finer 5-km ice sheet grid. During a twenty-first-century simulation driven by representative concentration pathway 8.5 (RCP8.5) forcing, the SMB decreases from 372 ± 100 Gt yr⁻¹ in 1980-99 to −78 ± 143 Gt yr⁻¹ in 2080-99. The 2080-99 near-surface temperatures over the GIS increase by 4.7 K (annual mean) with respect to 1980-99, only 1.3 times the global increase (+3.7 K). Snowfall increases by 18%, while surface melt doubles. The ablation area increases from 9% of the GIS in 1980-99 to 28% in 2080-99. Over the ablation areas, summer downward longwave radiation and turbulent fluxes increase, while incoming shortwave radiation decreases owing to increased cloud cover. The reduction in GIS-averaged July albedo from 0.78 in 1980-99 to 0.75 in 2080-99 increases the absorbed solar radiation in this month by 12%. Summer warming is strongest in the north and east of Greenland owing to reduced sea ice cover. In the ablation area, summer temperature increases are smaller due to frequent periods of surface melt. ANT1103686